ORGANISASI FORMAL DAN INFORMAL: TINJAUAN KONSEP, PERBANDINGAN, DAN STUDI KASUS - Irawan, Bambang (Jurnal Administrative Reform, 2018)
Formal organizations and informal organizations are one form of organizational entity that is important in the study of management and public administration. This paper tries to examine the formal and informal organizations in concept, comparison, and existing case study models so that a comprehensive understanding of the issues of formal and informal organizations can be obtained in the study of management and public administration.Keyword: formal, informal, organization